Why are economists so different? Nature, nurture, and gender effects in a simple trust game - Justus Haucap; Andrea Müller (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
We analyze the behavior of 577 economics and law students in a simple binary trust experiment. While economists are both significantly less trusting and less trustworthy than law students, this difference is largely due to differences between female law and economics students. While female law students are already different in nature (during the first term of study) from female economists, the gap between them also widens more drastically over the course of their study compared to their male counterparts. This finding is rather critical as the detailed composition of students is typically neglected in most experiments.
Keywords: A12; A22; C35; C91; 330; Gender Effects; Trust Game; Economists; Nature; Nurture